PENGARUH LINGKUNGAN KERJA, KOMPENSASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA CV. MAJESTA NUSANTARA BANYUWANGI - Cahyanti, Lutfita Seftian Dwi; Setyawati, Trias; Puspitadewi, Ira (Growth, 2022)
Competition in the business world is getting tougher causing companies to be required to be able to increase competitiveness to maintain the survival of the company. Human resources are the biggest capital for the company, therefore in developing human resources the most important factor is improving the performance of its employees first, an employee who has high and good performance can support the achievement of the goals and objectives set by the company. In this study the authors raised the dynamics of employee performance contained in the CV. Majesta Nusantara Banyuwangi. CV. Majesta Nusantara Banyuwangi is engaged in the field of general suppliers, suppliers of materials & safety equipment, suppliers of environmental management materials & equipment, and printing. At present there are still many employees whose performance is not optional in terms of discipline so that there is poor employee performance. This study aims to examine and analyze the influence of the work environment, compensation and work discipline on employee performance at CV. Majesta Nusantara Banyuwangi. The population in this study were 36 respondents from CV employees. Majesta Nusantara Banyuwangi. The analysis tool uses multiple linear regression. The results of the study prove that the work environment, compensation and work discipline have a positive and significant effect on employee performance at CV. Majesta Nusantara Banyuwangi.